Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.4830
|View full text |Cite
|
Sign up to set email alerts
|

SAT0601 Anti-il6-receptor tocilizumab in graves’ orbitopathy. multicenter study of 29 patients

Abstract: ObjectivesTo assess the efficacy of Tocilizumab (TCZ) in refractory thyroid associated orbitopathy (TAO) due to Grave’s disease.MethodsMulticenter study of 29 patients with TAO refractory to conventional immunosuppressive therapy.ResultsWe studied 29 patients (58 eyes) (23 women/6 men); mean age at diagnosis 48.79±12.39 years. Besides oral corticosteroids and before the onset of TCZ, patients had been treated with pulses of intravenous methylprednisolone (n=24), methotrexate (n=2) and other drugs (methimazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Tocilizumab fue usado como monoterapia en 43 pacientes. Después de 7 meses de tratamiento en 10 casos se presentó remisión completa de la orbitopatía tiroidea, mejoría de la enfermedad en 12 pacientes y estabilidad del proceso in lamatorio en 3 pacientes; y en 2 casos la terapia fue ine icaz (19).…”
Section: Discussionunclassified
“…Tocilizumab fue usado como monoterapia en 43 pacientes. Después de 7 meses de tratamiento en 10 casos se presentó remisión completa de la orbitopatía tiroidea, mejoría de la enfermedad en 12 pacientes y estabilidad del proceso in lamatorio en 3 pacientes; y en 2 casos la terapia fue ine icaz (19).…”
Section: Discussionunclassified
“…A number of studies have shown that TCZ is safe and effective in treating TAO patients who were glucocorticoid insensitive. TCZ was also demonstrated to block the inflammatory cascade, improve clinical performance, and reduce CAS,[ 51 52 53 54 ] but it needs to be further verified in the clinical application. A variety of TNF-α monoclonal antibodies, such as etanercept, infliximab, and adalimumab, have shown good efficacy in TAO,[ 55 56 57 ] however most studies are case reports and large-scale population based studies have not been carried out.…”
Section: Cytokinesmentioning
confidence: 99%
“…The blockade of IL-6 and the PD-1 axis has been shown to have synergistic antitumour effects through the induction of cytotoxic T cells and the inhibition of in vivo tumourigenesis in animal studies [ 55 , 56 ]. Anti-IL-6 receptor antibodies have also yielded rapid and sustained improvement in various ocular parameters in patients with refractory Graves’ orbitopathy [ 57 ]. A personalised strategy for patients highlights the importance of inter-disciplinary collaboration between clinical oncology and ophthalmology.…”
Section: Use Of Immune Checkpoint Inhibitors and Thyroid Eye Disease-mentioning
confidence: 99%